Peningkatan Tata Kelola Ayam Pedaging di Desa Teruwai Kecamatan Pujut Kabupaten Lombok Tengahudul Artikel - Muh. Prasetyo Nugroho; Hermansyah; M. Taqiuddin; Anwar Fachry; Resky Amalyadi; Aden Dilaga (Universitas Mataram, 2026)
This community service program aimed to improve the management capacity of broiler chicken farming conducted by the UD Tui Jati farmer group in Teruwai Village, Pujut District, Central Lombok Regency. The main problems encountered by the farmers included weak business planning, limited organizational management, lack of systematic financial recording, and inadequate marketing management. The program was implemented using a participatory approach through preliminary observation, extension activities, group discussions, training, and technical assistance focusing on business planning, financial administration, organizational strengthening, and business evaluation. The results indicated an improvement in farmers’ understanding and managerial capacity in managing broiler farming enterprises more systematically. Farmers began implementing simple financial records, improving group coordination, and conducting basic business evaluations. In addition, the strengthening of farmer group institutions supported collective learning and business coordination among members. The program contributed to improving farm management practices, increasing business efficiency, and supporting the sustainability of smallholder broiler farming enterprises.